Dampak konsumsi pangan tinggi kandungan indeks glikemik dengan kejadian diabetes mellitus tipe-II di Kabupaten Pidie - Mulmuliana Mulmuliana; Rachmawati Rachmawati (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: Type II diabetes mellitus is a disorder of glucose metabolism disease in which the body fails to control the glucose that enters food, so blood sugar levels become high. One of the factors causing type II diabetes mellitus is the habit of consuming foods with a high glycemic index.Objective: This study aims to determine the relationship between high glycemic index food consumption and the incidence of type II diabetes mellitus.Method: The cross-sectional research design was carried out in Pidie Regency in 2021. A sample of 50 aged 30-65 years was taken purposively. Data collection of high glycemic index food consumption using a questionnaire and type-II diabetes mellitus based on examination of blood sugar levels. Statistical analysis used the Chi-square test at 95% CI.Results: The study's results have found that people with diabetes mellitus very often consume foods containing a high glycemic index, which is 40.0%. There was a significant effect between the consumption of high glycemic index food and the incidence of type II diabetes mellitus (p= 0.003).Conclusion: Consumption of food with a high glycemic index significantly impacts the incidence of type-II diabetes mellitus in the 30-59 year age group. Keywords